Theory Plan of Behavior Perspective: Exploring Sustainable Product Remanufacture and its Impact on Purchase Intentions - Ni Putu Yulia Mawarisma; Nilna Muna (Quantitative Economics and Management Studies, 2024)
Environmental concerns globally, encompassing issues like pollution, global warming, and ozone depletion, highlight the urgency for sustainability measures. Within the realm of green initiatives, understanding remanufactured products emerges as a facet of environmental literacy. This research addresses prior inconsistencies by examining mediating factors specifically, the impact of value consciousness and awareness of green products on the inclination to buy remanufactured goods. Collected data through distributing 270 questionnaires which is a sample of data from the entire population of Bali province, Structural Equation Modeling (SEM) via AMOS software version 23 was employed for analysis. Findings indicate the pivotal roles of green knowledge of remanufactured products, value consciousness, and awareness in shaping the purchase intention to eco-friendly items. Consequently, this study bears implications for companies aiming to advance sustainable products, and it offers insights for policymakers and industry stakeholders to formulate strategies that foster consumer awareness and green product development.